Learning to dashboard: modes of producing and deploying data visualising technologies in higher distance education. - Vanermen, Lanze; Vlieghe, Joris; Decuypere, Mathias (Discourse: Studies in the Cultural Politics of Education, 2025)
Educational dashboards are increasingly prevalent visualising technologies that display data from educational processes to help learners and educators track learning pathways, alert for deviations, and make interventions. This study contributes to critical studies on data visualisations in education by examining dashboards in higher distance education. Inspired by science and technology studies (STS), it investigates several modes of relating to educational dashboards at one distance university, focusing on their production and deployment. Ethnographic findings show how dashboards are produced through public-private, interdisciplinary collaboration and (made to) align with predominant techno-pedagogical ideas, often by persuading university students to use technologies correctly. When deployed, students learn to filter relevant information, practice self-monitoring, and (re)examine dashboard usage. The case exemplifies a 'dashboarding of learning' and 'learning to dashboard', indicating that dashboards not only enter educational practices but also encourage actors – sometimes unsuccessfully – to understand and realise their education in line with specific techno-pedagogical ideas.